Um estudo frankfurtiano sobre a relação indivíduo e sociedade em Freud - Carretero, Gustavo Henrique (2011)
The study aimed to identify how categories individual and society they relate and how they are theorized in Freud s work, as well as reflect on such elements from the particular conception of: the Society of Critical Theory proposed by the first generation of the Frankfurt School, especially Adorno and Marcuse. To this end, they were selected three representative works of Freud s thinking about the relationship between individual and society, which were: Totem and Taboo , Psychology of Groups and Analysis of the Ego and Malaise in Civilization . This material was analyzed according to the contributions of Adorno and Marcuse. The study indicates that, for the frankfurtian authors, culture appears as a factor mediating the relationship between individual and society to Freud, however, the author defends the cultural processes at the expense of freedom and autonomy of individuals. Such aspect constitutes itself how one of the contradictions of Freud s though, given that psychoanalysis is guided in the liberal model. Such element turns out in critical of decay of such model of constitution of the individual in the transition from competitive capitalism to monopolist. At the same time, the works of Freud suggests that the contradictions of culture end up being subjective to the individual. In addition, the emotional ambivalence generated by the contradictions of culture, is manipulated to become in accession of the individual goals to social goals. Adorno and Marcuse realize that the Freudian model points to the liberal individual and seek to reinterpret psychoanalysis, each in its own way, to the light of the transformations of capitalism and new social cultural settings. It is considered the opinion of recent authors, suported by lacanians concepts which differ from the Frankfurtians, disagreeing that the structural conception of the subject in its relation to language, implies the denial of the historicity of social bonds in which they occur